FINANCIAL FEASIBILITY ANALYSIS OF BOILER CHICKEN (Gallus domesticus) BUSINESS IN GAMPONG SEUMIRAH NISAM DISTRICT BETWEEN ACEH UTARA DISTRICT (Case Study: Business Entity Owned by Gampong Seumirah) - Muhammad Alfaris; Jamilah Jamilah; Irada Sinta (Jurnal Mahasiswa Agribisnis, 2023)
Broiler farming business is one of the businesses that has the potential to produce meat and increase protein consumption for the community. Broiler chickens are fast-growing chickens and can be harvested in a short time. However, in this boiler chicken farm business, it requires large costs for the manufacture of cages and operational costs. The research was conducted in Seumirah, Nisam Antara District, North Aceh Regency. The aim of this research is to analyze the financial feasibility of boiler chicken farming business. The data analysis method used in this research is quantitative descriptive analysis. The results of the study showed that BUMG Seumirah's boiler chicken farm located in Gampong Seumirah, Nisam Antara District, North Aceh Regency was feasible. This can be seen from the NPV value of Rp. 13,136,583,520. The Net B/C value is 14.1 > 1 IRR value obtained is 73.63% > the current interest rate (6%) BEP is obtained at 11 years 8 months 12 days.Keywords: a boiler chicken farming business, financial feasibility.